A study on the use of computer based english language placement tests as measurements of English language proficiency among university students / Normah Abdullah … [et al.] - Abdullah, Normah; Ramlan, Zarina Suriya; Ismail, Othman; Salleh, Fairoz; Kasim, Noraida (UiTM Press, 2016)
This study reports the use of English Placement Tests (EPTs) supported by an e-engine software to test English language skills in Listening and Reading among new Universiti Teknologi MARA (UiTM) Diploma students of the November 2014-April 2015 cohort. The objective of the study was to exempt students with excellent English language proficiency from taking the University’s basic English language course offered in semester one (ELC120/Integrated Language Skills: Listening). Results of the study reveal that the majority of the students (97.5%) did not meet the required scores in both Listening and Reading for exemption to be given. Challenges in the implementation of the test and the participation of the students in the pilot study are discussed. Implications of the study to the University stakeholders are highlighted.